If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4=(4x+10)
We move all terms to the left:
4-((4x+10))=0
We calculate terms in parentheses: -((4x+10)), so:We get rid of parentheses
(4x+10)
We get rid of parentheses
4x+10
Back to the equation:
-(4x+10)
-4x-10+4=0
We add all the numbers together, and all the variables
-4x-6=0
We move all terms containing x to the left, all other terms to the right
-4x=6
x=6/-4
x=-1+1/2
| x+2+x-8=90 | | 3x+36=63-7x | | 6/5y-1/3y=-2.6 | | (1.5-2.5x)=6-(2x+4) | | 1/3(x+2/5)=-23/15 | | 5-1x=3x-18 | | 5.4+0.2x=-1.4+8.6= | | 1/4•43+63+57+x=55 | | 15x-4=146 | | 1/2(x-3/5)=-13/10 | | (1/4)(43+63+5+x)=55 | | -5m=9−4m | | 35w=70 | | 14g-8-2g=16 | | 10x(x-5)=9(x-5) | | (1+3i)(1-3i)=0 | | (1+3i)(1+3i)=0 | | 11=v/2-12 | | 25.50+x=1836 | | 1.6+0.4x=3.4+0.2x | | 3x-2=x=10 | | c2–20=-18 | | 2(5x-4)=9x+17 | | 8d=4d=6d-9=5d | | 2(5x-4)=6x+9 | | 8d+4d+6d-9=5d | | p+6+p-3=1+4p | | 17+w=25 | | -2(6g−3)= | | 4(8-y=2y+16 | | -2x-5=2-3x | | n-35=-72 |